Influence of sulphur and plant growth regulators on yield, quality and nutrient uptake in summer peanut (Arachis hypogaea) - Saini, Chetram; Jain, N.K. (Annals of Agricultural Research, 2017)
A field experiment was carried out during summer 2014 in a medium black clayey soil at Instructional Farm, Department of Agronomy, College of Agriculture JAU, Junagadh (Gujarat) to evaluate the influence of sulphur and plant growth regulators on yield, quality and nutrient uptake in summer peanut (Arachis hypogaea). Significantly higher pod and haulm yields was recorded due to application of 20 kg S ha–1 by 21.6 and 12.9% over control, respectively. On the other hand, kernel, biological and oil yields increased significantly up to 40 kg S ha–1 by 44.7, 24.2 and 54.6% over the control, respectively. Significantly higher protein and oil contents in peanut kernels were recorded at 60 kg S ha–1 over control and 20 kg S ha–1 and was at par with 40 kg S ha–1. Sulphur application up to 40 kg ha–1 significantly increased total N, P and S uptake by peanut. Application of NAA @ 40 ppm twice at 25 and 50 DAS significantly enhanced pod, haulm, kernel and biological yields by 33.2, 18.4, 42.8, and 23.8% over control, respectively and was at par with GA3 @ 20 ppm twice at 25 and 50 DAS. Application of GA3 @ 20 ppm twice at 25 and 50 DAS recorded the highest protein and oil contents, oil yield, N, P and S uptake by peanut over rest of the treatments.